AB1155 CORRELATION BETWEEN NAILFOLD VIDEOCAPILLAROSCOPY PATTERNS, LEFT VENTRICLE DYSFUNCTION AND PULMONARY DISEASE IN SYSTEMIC SCLEROSIS. (June 2019) - Lucio, Monaco; Masini, Francesco; Gjeloshi, Klodian; Pinotti, Emanuele; Ferrara, Roberta; Salvatore, Teresa; Cuomo, Giovanna
Abstract : Background: Systemic Sclerosis (SSc) is a multisystem connective disease characterized by a microvascular damage, which leads to systemic fibrosis, immune dysregulation and progressive involvement of internal organs [1]. According to the classification of the morphological aspects, into the scleroderma pattern proposed by Cutolo et al. are described the early, active and late patterns. Objectives: The aim of our study is thus to report a correlation between specific nailfold videocapillaroscopy pattern and internal organ involvement. Methods: All enrolled patients were diagnosed for SSc, according to the American College of Rheumatology criteria and underwent an echocardiographic examination and a nailfold videocapillaroscopy. Myocardial function parameters considered were: global contractility (computed with the Simpson method), linear contractility (computed through the MAPSE) [2], diastolic dysfunction (through the analysis of the trans-mitral flow) [3]; whilst those of lung damage were: PAPs and the evaluation of the right ventricle contractility through the TAPSE [4]. Statistics were performed with SPSS 20 software, by using the Mann Whitney U Test and the Fisher Test. Results: We enrolled 27 patients, of which 16 showing "active pattern" and 11 "early pattern", compared to a group of 21 healthy controls. Of the 11 patients belonging to the "early" group, 1 resulted affected by diastolic dysfunction, whilst 3 had pulmonary hypertension, defined by PAPs ≥40 mmHg [4] (early vs controls; p=0.03). In the 16 patients of the "active" group. instead, 5 were found to have a diastolic dysfunction (active vs controls; p=0.01) and 6 pulmonary hypertension (active vs controls; p=0.003). In the group with "active" pattern we also observed a reduction in TAPSE compared to the control group (2, 0 ± 0, 2 vs 2, 2 ± 0, 2; p=0, 025) and compared to the group with early pattern (2, 0 ± 0, 2 vs 2, 2 ± 0, 3; p=0, 07). No presence of modifications in the global contractility emerged; however, we observed a progressive reduction of the MAPSE (controls 1.76 ± 0, 08; early 1.57 ± 0, 04; active 1.49 ± 0, 12), which resulted statistically significant among the different comparisons (controls vs early p=0.001; controls vs active p=0.0001; early vs active p=0.04). Conclusion: The analyses showed a strict correlation between the severity of the microvascoular alterations, reported by nailfold videocapilloroscopy, and the severity of the cardiopulmonary damage, expressed by an increase in the percentage of pulmonary hypertension, diastolic dysfunction and a progressive reduction of MAPSE and TAPSE. References: [1] LeRoy EC. Systemic sclerosis. A vascular perspective. Rheum Dis Clin North Am. [2] Ibadete Bytci, Left atrial change in early stages of heart failure with preserved ejection fraction. Echocardiography [3] Sherif F. Recommendations for the Evaluation of Left Ventricular Diastolic Function by Echocardiography. Journal of the American Society of Echocardiography [4] Luke S. Howard, Echocardiographic assessment of pulmonary hypertension: standard operating procedure. European Respiratory Review Disclosure of Interests: None declared